Energy storage element

By using a hydrophilized non-graphitic carbon active material layer without a binder in the storage element, the issue of output drop at high temperatures is addressed, resulting in improved performance and longevity.

JP7649461B2Active Publication Date: 2025-03-21GS YUASA CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2020154609
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-09-15
Publication Date
2025-03-21
Estimated Expiration
2040-09-15

AI Technical Summary

Technical Problem

Existing storage elements experience a significant drop in output when left at high temperatures, which affects their performance and efficiency.

Method used

The electric storage element incorporates an active material layer made of hydrophilized non-graphitic carbon without a binder, which enhances the dispersion and binding of active material particles, thereby maintaining output performance even at high temperatures.

Benefits of technology

This configuration effectively suppresses the decrease in output after being left at high temperatures, ensuring consistent performance and extended lifespan of the storage element.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007649461000002
    Figure 0007649461000002
  • Figure 0007649461000003
    Figure 0007649461000003
  • Figure 0007649461000004
    Figure 0007649461000004
Patent Text Reader

Abstract

To provide a power storage element in which a decrease in output after being left at high temperature is suppressed.SOLUTION: A power storage element includes an electrode having an active material layer containing active material particles, the active material layer contains hydrophilized non-graphitic carbon and does not contain a binder, and the content of the hydrophilized non-graphitic carbon is more than 4 mass%. Further, the active material layer contains particles of nickel-containing lithium transition metal composite oxide as the active material particles.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an energy storage element. [Background technology]

[0002] Patent Document 1 describes a positive electrode for a lithium ion secondary battery that contains a conductive additive, in which acetylene black having a hydrophilic functional group on the surface is used as the conductive additive, and the surface hydrophilic group rate of the acetylene black is 19.5% or more and 22.4% or less. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2015-176831 A Summary of the Invention [Problem to be solved by the invention]

[0004] An object of the present invention is to provide an energy storage element in which a decrease in output after being left at high temperatures is suppressed. [Means for solving the problem]

[0005] An electric storage device according to one aspect of the present invention includes an electrode having an active material layer including active material particles, The active material layer contains hydrophilized non-graphitic carbon and does not contain a binder. Effect of the Invention

[0006] In an energy storage device according to one aspect of the present invention, a decrease in output after being left at high temperatures is suppressed. [Brief description of the drawings]

[0007] [Figure 1] FIG. 1 is a perspective view of an energy storage element according to the present embodiment. [Diagram 2] FIG. 2 is a perspective view of the outermost periphery of the wound electrode body of the energy storage element according to this embodiment in a stretched state. [Diagram 3] FIG. 3 is a schematic diagram of an energy storage device including a plurality of energy storage elements according to this embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] First, an overview of an energy storage device 1 disclosed in this specification will be given.

[0009] An energy storage device 1 according to one aspect of the present invention includes an electrode having an active material layer containing active material particles, and the active material layer contains hydrophilized non-graphitic carbon and does not contain a binder.

[0010] In this energy storage device 1, a decrease in output power after being left at high temperatures can be suppressed.

[0011] Here, in the energy storage device 1, the content of the hydrophilized non-graphitic carbon in the active material layer may be more than 4 mass %.

[0012] In this energy storage device 1, the decrease in output after being left at high temperatures can be further suppressed.

[0013] Here, in the energy storage device 1, the active material layer may contain particles of a nickel-containing lithium transition metal composite oxide as the active material particles.

[0014] In this energy storage device 1, the decrease in output after being left at high temperatures can be further suppressed.

[0015] The configuration of an energy storage element, the configuration of an energy storage device, and a method for manufacturing an energy storage element according to an embodiment of the present invention, as well as other embodiments, will be described in detail. Note that the names of the components (components) used in each embodiment may differ from the names of the components (components) used in the background art.

[0016] <Configuration of Energy Storage Element> The electric storage element according to the embodiment of the present invention includes an electrode assembly 2 having a positive electrode 40, a negative electrode 50, and a separator 60, an electrolyte, and a case 3 that accommodates the electrode assembly 2 and the electrolyte. The electrode assembly 2 is usually a wound type in which the positive electrode 40 and the negative electrode 50 are wound in a stacked state with the separator 60 interposed therebetween, or a stacked type in which a plurality of positive electrodes 40 and a plurality of negative electrodes 50 are stacked with the separator 60 interposed therebetween. The electrolyte exists in a state that it is contained in the positive electrode 40, the negative electrode 50, and the separator 60. Hereinafter, a nonaqueous electrolyte secondary battery (particularly a lithium ion secondary battery, hereinafter also simply referred to as a "secondary battery") will be described as an example of an electric storage element, but there is no intention to limit the application of the present invention.

[0017] As shown in FIG. 1, the energy storage element 1 of this embodiment includes a wound electrode body 2 in a wound state and a case 3 that houses the electrode body 2. The energy storage element 1 also includes two external terminals (a positive electrode terminal 4 and a negative electrode terminal 5) that are attached to the case 3 with at least a part of the case 3 exposed or that are formed by at least a part of the case 3. The electrode body 2 is connected to the external terminals 4, 5 within the case 3 via a current collecting member or the like. The external terminals 4, 5 are attached to the case 3. The case 3 has a flattened rectangular parallelepiped shape and includes a case body 31 that opens toward one side and a long and narrow rectangular lid body 32 that covers the opening of the case body 31. The two external terminals 4, 5 are arranged spaced apart in the long side direction of the lid body 32. In the energy storage device 1 of this embodiment, the electrode body 2 is housed in the case 3 so that the winding axis direction of the electrode body 2 is the same as the long side direction of the lid 32 of the case 3.

[0018] As shown in Fig. 2, the electrode body 2 is formed by stacking a long sheet-like positive electrode 40, a long sheet-like negative electrode 50, and two long sheet-like separators 60, 60, and further winding them. In other words, the electrode body 2 is formed by winding a strip-like laminate including the positive electrode 40, the negative electrode 50, and the two separators 60, 60. The two separators 60, 60 are arranged so as to electrically insulate the positive electrode 40 and the negative electrode 50, respectively. In this embodiment, the electrode body 2 is a flat wound body.

[0019] (positive electrode) The positive electrode 40 has a positive electrode substrate 41 and a positive electrode active material layer 42 disposed directly or via an intermediate layer (not shown) on the positive electrode substrate 41. In this embodiment, the positive electrode active material layers 42 are laminated on both sides of the positive electrode substrate 41.

[0020] The positive electrode substrate 41 has electrical conductivity. Whether or not the positive electrode substrate 41 has electrical conductivity is determined by a volume resistivity of 10 7 The threshold value is Ω·cm. The material of the positive electrode substrate 41 is a metal such as aluminum, titanium, tantalum, stainless steel, or an alloy thereof. Among these, aluminum or an aluminum alloy is preferable from the viewpoints of potential resistance, high conductivity, and cost. The positive electrode substrate 41 may be a foil, a vapor deposition film, or the like, and foil is preferable from the viewpoint of cost. Therefore, aluminum foil or aluminum alloy foil is preferable as the positive electrode substrate 41. Examples of aluminum or an aluminum alloy include A1085, A3003, and the like specified in JIS-H-4000 (2014).

[0021] The average thickness of the positive electrode substrate 41 is preferably 3 μm to 50 μm, more preferably 5 μm to 40 μm, further preferably 8 μm to 30 μm, and particularly preferably 10 μm to 25 μm. By setting the average thickness of the positive electrode substrate 41 within the above range, it is possible to increase the strength of the positive electrode substrate 41 and to increase the energy density per volume of the secondary battery.

[0022] The intermediate layer is a layer disposed between the positive electrode substrate 41 and the positive electrode active material layer 42. The intermediate layer contains conductive particles such as carbon particles, thereby reducing the contact resistance between the positive electrode substrate 41 and the positive electrode active material layer 42. The configuration of the intermediate layer is not particularly limited, and includes, for example, a resin binder and conductive particles.

[0023] The positive electrode active material layer 42 includes a positive electrode active material. In this embodiment, the positive electrode active material layer 42 preferably includes the positive electrode active material and a conductive agent. In this case, the conductive agent includes at least hydrophilized non-graphitic carbon, and the positive electrode active material layer 42 does not include a binder. The positive electrode active material layer 42 includes optional components such as a thickener and a filler as necessary.

[0024] The positive electrode active material can be appropriately selected from known positive electrode active materials. A material capable of absorbing and releasing lithium ions is usually used as the positive electrode active material for a lithium ion secondary battery. Examples of the positive electrode active material include lithium transition metal composite oxides (lithium transition metal composite oxides having an α-NaFeO2 type crystal structure or a spinel type crystal structure), polyanion compounds, chalcogen compounds, sulfur, and the like. Examples of lithium transition metal composite oxides having an α-NaFeO2 type crystal structure include Li[Li x Ni (1-x) ]O2(0≦x<0.5), Li[Li x Ni γ Co (1-x-γ )]O2(0≦x<0.5, 0<γ<1), Li[Li x Co (1-x) ]O2(0≦x<0.5), Li[Li x Ni γ Mn (1-x-γ) ]O2(0≦x<0.5, 0<γ<1), Li[Li x Ni γ Mn β Co (1-x-γ-β) ]O2(0≦x<0.5, 0<γ, 0<β, 0.5<γ+β<1), Li[Li x Ni γ Co β Al (1-x-γ-β) ]O2 (0≦x<0.5, 0<γ, 0<β, 0.5<γ+β<1), etc. Lithium transition metal composite oxides with spinel crystal structure include LixMn2O4, Li x Ni γ Mn (2-γ)O4, etc. Examples of polyanion compounds include LiFePO4, LiMnPO4, LiNiPO4, LiCoPO4, Li3V2(PO4)3, Li2MnSiO4, Li2CoPO4F, etc. Examples of chalcogen compounds include titanium disulfide, molybdenum disulfide, molybdenum dioxide, etc. Atoms or polyanions in these materials may be partially substituted with atoms or anion species of other elements. The surfaces of these materials may be coated with other materials. In the positive electrode active material layer 42, one of these materials may be used alone, or two or more of them may be mixed and used.

[0025] In a preferred embodiment, the positive electrode active material is composed of the lithium transition metal composite oxide containing Li and a transition metal. For example, the lithium transition metal composite oxide is exemplified by a nickel-containing lithium transition metal composite oxide containing at least lithium (Li) and nickel (Ni) as constituent elements. Such a composite oxide may have a layered α-NaFeO2 type (i.e., an X-ray diffraction pattern that can be assigned to the space group R3-m) crystal structure. In addition, the lithium transition metal composite oxide is exemplified by a cobalt-containing lithium transition metal composite oxide containing at least lithium (Li) and cobalt (Co) as constituent elements. Such a composite oxide may have a layered α-NaFeO2 type crystal structure. In addition, the lithium transition metal composite oxide is exemplified by a manganese-containing lithium transition metal composite oxide containing at least lithium (Li) and manganese (Mn) as constituent elements. Such a composite oxide may have a layered α-NaFeO2 type crystal structure or a spinel type crystal structure.

[0026] The positive electrode active material preferably contains the nickel-containing lithium transition metal composite oxide. When the positive electrode active material contains the nickel-containing lithium transition metal composite oxide, the hydrophilized non-graphitic carbon can be easily and satisfactorily dispersed in the positive electrode active material layer 42. This makes it possible to more sufficiently suppress a decrease in the output of the energy storage device 1 after it is left at high temperatures.

[0027] In the nickel-containing lithium transition metal composite oxide, the molar ratio (Ni / Me) of nickel (Ni) to the total moles of the transition metal (Me) contained is not particularly limited. The molar ratio (Ni / Me) may be, for example, 10 mol% or more, preferably 20 mol% or more, and more preferably 30 mol% or more. By using a nickel-containing lithium transition metal composite oxide containing nickel at such a ratio, the output reduction effect of the energy storage element 1 after being left at high temperature can be more fully exhibited. In some embodiments, the molar ratio (Ni / Me) related to nickel may be 50 mol% or more, or 60 mol% or more (e.g., 80 mol% or more). On the other hand, the ratio (Ni / Me) may be, for example, 100 mol% or less, or 90 mol%. In some embodiments, the ratio (Ni / Me) may be 85 mol% or less, or 80 mol% or less (e.g., 60 mol% or less).

[0028] The nickel-containing lithium transition metal composite oxide preferably further contains at least one of manganese and cobalt as a transition metal, and more preferably further contains both manganese and cobalt. A more suitable example is a layered nickel-cobalt-manganese-containing lithium transition metal composite oxide (NCM) containing cobalt and manganese as constituent elements in addition to lithium and nickel. As such an NCM, an NCM in which the molar ratio (Ni / Me) of the nickel is greater than both the molar ratio (Mn / Me) of manganese (Mn) in the total number of moles of the transition metal (Me) contained and the molar ratio (Co / Me) of cobalt (Co) in the total number of moles of the transition metal (Me) contained, or an NCM containing Ni, Co, and Mn in approximately the same ratio is preferable.

[0029] A suitable example of the nickel-containing lithium transition metal composite oxide is, for example, a composite oxide represented by the following composition formula (1). Li x Ni a Co b Mn c M d Oe Composition formula (1) [In composition formula (1), M is at least one element selected from elements other than Li, Ni, Co, and Mn, 0 < x ≤ 1.3, a + b + c + d = 1, 0 < a ≤ 1, 0 ≤ b < 1, 0 ≤ c < 1, 0 ≤ d < 1, and 1.7 ≤ e ≤ 2.3 are satisfied.]

[0030] Specifically, in the above composition formula (1), M is, for example, one or more elements selected from the group consisting of Al, Mg, Zr, W, Ti, Ca, K, Na, Si, B, F, Bi, Er, and Lu. Among these, as M, any one of Al, B, Zr, W, and Ti, or a combination of two or more is preferable. Further, in composition formula (1), x is preferably 1 or more, and may be 1. From the viewpoint of more sufficiently suppressing the output reduction of the power storage element 1, etc., a is preferably 0.3 or more, more preferably 1 / 3 or more. Also, a may be less than 1, preferably 0.9 or less, more preferably 0.8 or less. In some embodiments, a may be, for example, 0.6 or less, 0.5 or less. b is preferably greater than 0, more preferably 0.05 or more. In some embodiments, b may be 0.1 or more, 0.2 or more, 0.3 or more. Also, b is preferably less than 1, more preferably 0.5 or less. In some embodiments, b may be 1 / 3 or less, 0.2 or less, 0.1 or less. c is preferably greater than 0, more preferably 0.05 or more. In some embodiments, c may be 0.1 or more, 0.2 or more, 0.3 or more. Also, c is preferably less than 1, more preferably 0.5 or less. In some embodiments, c may be 1 / 3 or less, 0.2 or less, 0.1 or less. d is preferably 0.1 or less, and may be substantially 0. e is a value determined within the range of 1.7 ≤ e ≤ 2.3 so as to satisfy the charge neutrality condition, and may be substantially 2.]

[0031] The positive electrode active material is in the form of a powder composed of particles before being mixed into the mixture composition for the positive electrode active material layer. The positive electrode active material typically includes secondary particles formed of primary particles. The active material particles of the positive electrode 40 may have a hollow structure in which voids are formed inside the secondary particles formed of the primary particles. When the active material particles of the positive electrode 40 have the above-mentioned hollow structure, hydrophilized non-graphitic carbon enters the voids (typically hollow parts) of the secondary particles. This makes it possible to more effectively exhibit the above-mentioned performance improvement effect (for example, the effect of suppressing the output reduction of the electric storage device after being left at high temperature). The average particle diameter D1 of the active material particles of the positive electrode 40 is preferably, for example, 0.1 μm or more and 20 μm or less. The average particle diameter D1 of the positive electrode active material particles is more preferably 0.5 μm or more, further preferably 0.8 μm or more, and particularly preferably 1 μm or more (for example, 3 μm or more). Moreover, the average particle diameter D1 of the positive electrode active material particles is more preferably 15 μm or less, further preferably 10 μm or less, and particularly preferably 5 μm or less. By having the average particle diameter D1 of the positive electrode active material particles within the above range, the performance improvement effect of the hydrophilized non-graphitic carbon (for example, the effect of suppressing the output reduction of the power storage device after being left at high temperature) can be more fully exhibited. Furthermore, by making the average particle diameter D1 of the active material particles of the positive electrode 40 equal to or greater than the above lower limit, the production or handling of the positive electrode active material becomes easier. By making the average particle diameter D1 of the active material particles of the positive electrode 40 equal to or less than the above upper limit, the electronic conductivity of the positive electrode active material layer 42 is further improved. Note that, when a composite of the positive electrode active material and another material is blended in the positive electrode active material layer 42, the average particle diameter of the composite is taken as the average particle diameter D1 of the active material particles. "Average particle size D1" refers to the value at which the volume-based cumulative distribution calculated in accordance with JIS-Z-8819-2 (2001) is 50%, based on the particle size distribution measured in accordance with JIS-Z-8825 (2013) using a laser diffraction / scattering method for a solution obtained by diluting particles with a solvent.

[0032] In order to obtain a powder containing particles of a predetermined particle size, a pulverizer, a classifier, etc. are used. Examples of the pulverization method include a method using a mortar, a ball mill, a sand mill, a vibration ball mill, a planetary ball mill, a jet mill, a counter jet mill, a swirling airflow type jet mill, or a sieve. During pulverization, wet pulverization in the presence of water or an organic solvent such as hexane can also be used. As a classification method, a sieve, an air classifier, etc. are used as necessary for both the dry and wet methods.

[0033] The content of the positive electrode active material in the positive electrode active material layer 42 is preferably 50% by mass to 99% by mass, more preferably 70% by mass to 98% by mass, and even more preferably 80% by mass to 96% by mass (e.g., 85% by mass to 95% by mass). By setting the content of the positive electrode active material within the above range, it is possible to achieve both a high energy density of the positive electrode active material layer 42 and ease of production.

[0034] In this embodiment, the positive electrode active material layer 42 does not contain a binder, and contains hydrophilized non-graphitic carbon as a conductive agent. Note that "does not contain a binder" means that the binder content in the positive electrode active material layer 42 is less than 3000 ppm (less than 0.3 mass%).

[0035] The binder is a conventionally known component (e.g., a resin component) that is generally used in the positive electrode active material layer of a conventional storage element.Specific examples of the binder include polytetrafluoroethylene (PTFE), tetrafluoroethylene-perfluoroalkylvinylether copolymer (PFA), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), ethylene-tetrafluoroethylene copolymer (ETFE), vinyl acetate copolymer, styrene-butadiene rubber (SBR), acrylic acid-modified SBR, ethylene-propylene-diene rubber (EPDM), sulfonated EPDM, fluorine-containing rubber, gum arabic, polyvinylidene fluoride (PVDF), polyvinylidene chloride (PVDC), polyethylene (PE), polypropylene (PP), polyethylene oxide (PEO), polypropylene oxide (PPO), polyethylene oxide-propylene oxide copolymer (PEO-PPO), etc. In the positive electrode active material layer of a conventional energy storage element, these binders bind the positive electrode active materials to each other via the binder, but they swell with the nonaqueous electrolyte at high temperatures and act as a component that can increase the electrical resistance, which can be a factor that limits the reduction in electrical resistance. In addition, these binders can be unevenly distributed due to migration during the preparation of the positive electrode, causing uneven charge and discharge reactions, which can be a factor that causes deterioration.

[0036] In contrast, in the energy storage device 1 of this embodiment, the positive electrode active material layer 42 does not contain a binder, so that the binder is prevented from swelling with the non-aqueous electrolyte at high temperatures, which causes the active material particles to lose electrical contact with each other. In addition, since the positive electrode active material layer 42 contains hydrophilized non-graphitic carbon, the hydrophilized non-graphitic carbon serves as a substitute for the binder, and the active material particles can maintain electrical contact with each other even at high temperatures. Furthermore, in the energy storage device 1 of this embodiment, the unevenness of the charge / discharge reaction caused by the uneven distribution of the binder and the deterioration associated with the unevenness are less likely to occur compared to an energy storage device containing a binder in the positive electrode active material layer. Therefore, the resistance of the positive electrode active material layer 42 can be prevented from increasing even at high temperatures. This can prevent the output of the energy storage device 1 from decreasing after it is left at high temperatures.

[0037] The hydrophilized non-graphitic carbon is a carbonaceous material other than graphite that has been hydrophilized. The hydrophilization is a treatment that increases the surface free energy (enhances wettability). Examples of the hydrophilized non-graphitic carbon include amorphous carbon, hard carbon, soft carbon, carbon black, and carbon fiber, each of which has been hydrophilized. Carbon black is preferred as the non-graphitic carbon. These non-graphitic carbons have a low crystallinity compared to graphite, and therefore have a moderate flexibility. Therefore, even if the positive electrode 40 repeatedly expands and contracts due to charging and discharging, the shape of the positive electrode 40 can be appropriately maintained. Examples of the non-graphitic carbon include carbonaceous materials derived from resins, carbonaceous materials derived from petroleum pitch, petroleum coke, carbonaceous materials derived from petroleum coke, carbonaceous materials derived from plants, and carbonaceous materials derived from alcohol.

[0038] It is preferable that a hydrophilic functional group is present on the surface of the hydrophilized non-graphitic carbon. Examples of the hydrophilic functional group include functional groups containing oxygen (O), specifically, -OH, or acidic functional groups containing >C=O. Examples of the acidic functional group containing -OH include hydroxyl groups, sulfo groups, and phenol groups. Examples of the acidic functional group containing >C=O include lactone groups, aldehyde groups, and ketone groups. Examples of the acidic functional group containing both -OH and >C=O include carboxy groups. Among these acidic functional groups, carboxy groups, ketone groups, hydroxy groups, and sulfo groups are preferred, and carboxy groups and hydroxy groups are particularly preferred. This type of hydrophilic functional group can be bonded to functional groups such as hydroxyl groups present on the surface of the positive electrode active material by dehydration condensation. This allows the positive electrode active materials to be firmly bonded to each other via the non-graphitic carbon without using a binder, and also allows the positive electrode active material to be firmly bonded to the positive electrode substrate 41 via the non-graphitic carbon.

[0039] In a preferred embodiment, the acidic functional group present on the surface of the hydrophilized non-graphitic carbon includes a carboxy group. When a carboxy group is present on the particle surface of the hydrophilized non-graphitic carbon, more of the carboxy group is anionized (-COO - ). This increases the electrostatic repulsion between the hydrophilized non-graphitic carbon particles. For example, when the above-mentioned nickel-containing lithium transition metal composite oxide is used as the positive electrode active material to prepare a positive electrode mixture composition, the mixture composition is likely to become alkaline due to the carboxyl groups present on the surfaces of the non-graphitic carbon particles. When the positive electrode active material layer 42 is prepared by applying this mixture composition onto the positive electrode substrate 41, the electrostatic repulsion between the hydrophilized non-graphitic carbon particles increases. This at least suppresses the aggregation between the non-graphitic carbon particles, and the particles are more sufficiently dispersed, resulting in the formation of a positive electrode active material layer 42 with a good dispersion state. Since the output performance of the electric storage element 1 can be improved to the extent that the positive electrode active material layer 42 is well dispersed, the decrease in output of the electric storage element 1 after being left at high temperature can be further suppressed. In addition, when the acidic functional groups present on the particle surfaces of the hydrophilized non-graphitic carbon contain hydroxyl groups, the aggregation of the non-graphitic carbon particles is similarly suppressed and the particles are more thoroughly dispersed, resulting in the formation of a positive electrode active material layer 42 in a well-dispersed state.

[0040] In this embodiment, the hydrophilized non-graphitic carbon preferably has a physical property such that the amount of hydrophilic functional groups per unit mass of the non-graphitic carbon based on neutralization titration is 100 μmol / g or more. By blending such hydrophilized non-graphitic carbon in the positive electrode active material layer 42, the positive electrode active materials can be more firmly bound to each other via the hydrophilized non-graphitic carbon without using a binder. From the viewpoint of more firmly binding, the amount of the hydrophilic functional groups is preferably 200 μmol / g or more, more preferably 300 μmol / g or more, and even more preferably 400 μmol / g or more. In some embodiments, the amount of the hydrophilic functional groups may be 500 μmol / g or more, or may be 800 μmol / g or more (for example, 1000 μmol / g or more). The upper limit of the amount of the hydrophilic functional groups is not particularly limited. From the viewpoints of ease of production and ease of handling during preparation of the positive electrode active material layer 42, the upper limit of the amount of the hydrophilic functional group is suitably 2000 μmol / g or less, preferably 1800 μmol / g or less, and more preferably 1500 μmol / g or less. In some embodiments, the amount of the hydrophilic functional group may be 1300 μmol / g or less, or may be 1200 μmol / g or less.

[0041] The neutralization titration is carried out as follows. In detail, a predetermined amount (e.g., 2 g) of hydrophilized non-graphitic carbon is dispersed in an aqueous sodium bicarbonate solution (e.g., 0.5 L of an aqueous sodium bicarbonate solution having a concentration of 0.976 mol / L). The dispersion is shaken for 6 hours, and then the hydrophilized non-graphitic carbon is separated by filtration. The filtrate is neutralized titrated with an aqueous sodium hydroxide solution (e.g., an aqueous sodium hydroxide solution having a concentration of 0.05 mol / L), and the amount of hydrophilic functional groups (μmol / g) per unit mass of the hydrophilized non-graphitic carbon can be calculated based on the titration amount up to the neutralization point near pH 8.

[0042] In this embodiment, the hydrophilized non-graphitic carbon preferably has physical property values ​​determined by the following measurement method. Specifically, 50 mg of non-graphitic carbon is dispersed in ion-exchanged water (e.g., 15 mL) to prepare a slurry. The pH of the slurry is measured at room temperature (e.g., 25°C) using a commercially available pH meter (e.g., Horiba, Ltd., product name "D-23"). The measured value is preferably 2.0 or more and 7.5 or less. From the viewpoint of further exerting the effect of suppressing the decrease in output of the energy storage element 1 after being left at high temperature, the pH of the slurry is preferably 2.2 or more and 7.2 or less, more preferably 2.5 or more and 7.0 or less, and even more preferably 2.8 or more and 6.6 or less.

[0043] The shape of the hydrophilized non-graphitic carbon is not particularly limited. Examples of the shape include spherical, deformed spherical, blocky, flaky, fibrous, and irregular shapes. The average particle size D2 (average primary particle size) of such non-graphitic carbon particles is preferably 30 nm or more. From the viewpoint of suppressing the aggregation of non-graphitic carbon particles, the average particle size D2 is preferably 50 μm or more, more preferably 80 μm or more, and even more preferably 100 μm or more. The upper limit of the average particle size D2 is suitably 300 nm or less. From the viewpoint of better exerting the function as a binder, the average particle size D2 is preferably 200 nm or less, more preferably 150 nm or less, and even more preferably 120 nm or less. The average particle size D2 can be measured, for example, by observation with an electron microscope. Specifically, a cut surface of the positive electrode active material layer 42 in the thickness direction is observed by an electron microscope, and the particle diameters of at least 100 particles (a predetermined number, for example, 100 to 1000 particles) are measured and averaged to measure the average particle diameter D2. The particle diameter is the diameter of the smallest circle (true circle) circumscribing each particle in the observed image.

[0044] In a preferred embodiment, at least a portion of the hydrophilized non-graphitic carbon particles is in contact with at least a portion of the positive electrode active material particles. In other words, at least a portion of the surface of the positive electrode active material particles is coated with the hydrophilized non-graphitic carbon particles. One positive electrode active material particle may be in contact with one non-graphitic carbon particle, or may be in contact with multiple non-graphitic carbon particles. Based on the above observation results using an electron microscope, it is preferable that 20% or more of the surface of the positive electrode active material particles is coated with the hydrophilized non-graphitic carbon particles as an average value in the positive electrode active material layer 42. The coverage ratio, which is the ratio of the area covered with the hydrophilized non-graphitic carbon particles to the total surface area of ​​the positive electrode active material particles, is preferably 30% or more, more preferably 40% or more, and even more preferably 50% or more. In this manner, since more of the surface of the positive electrode active material particles is covered with the hydrophilized non-graphitic carbon particles, the positive electrode active material particles can be more firmly bonded to each other via the hydrophilized non-graphitic carbon particles, and the positive electrode active material particles can be more firmly bonded to the positive electrode substrate 41.

[0045] In a preferred embodiment, the mass ratio of the hydrophilized non-graphitic carbon to the positive electrode active material in the positive electrode active material layer 42 may be, for example, 0.01 or more and 0.20 or less. Such a mass ratio is preferably 0.03 or more, and more preferably 0.05 or more. Moreover, such a mass ratio is preferably 0.15 or less, and more preferably 0.10 or less. When such a mass ratio is in the above numerical range, the above-mentioned effect that the positive electrode active material particles can be firmly bound to each other via the hydrophilized non-graphitic carbon can be more fully exhibited.

[0046] From the viewpoint of more fully exerting the above-mentioned effect of binding the positive electrode active material particles, it is preferable that the relationship between the average particle diameter D1 of the positive electrode active material particles and the average particle diameter D2 of the hydrophilized non-graphitic carbon particles satisfies 0.01≦(D2 / D1)≦0.05. By using a combination of the positive electrode active material particles and the hydrophilized non-graphitic carbon particles at a specific particle diameter ratio that satisfies the above-mentioned relationship, a positive electrode 40 in which the positive electrode active material particles are strongly bound to each other via the non-graphitic carbon particles and the positive electrode active material layer 42 is not easily peeled off from the positive electrode substrate 41 can be realized without blending a binder. The relationship between the average particle diameter D1 of the positive electrode active material particles and the average particle diameter D2 of the non-graphitic carbon particles is preferably 0.015≦(D2 / D1)≦0.04, more preferably 0.02≦(D2 / D1)≦0.035, and even more preferably 0.025≦(D2 / D1)≦0.03.

[0047] Hydrophilized non-graphitic carbon can be produced as follows. The hydrophilization treatment for increasing the hydrophilicity of non-graphitic carbon is not particularly limited, but typically a conventionally known hydrophilization treatment is adopted, such as a hydrophilization treatment for introducing hydrophilic functional groups onto the particle surface. Examples of hydrophilization methods include a method of subjecting non-graphitic carbon to an oxidation treatment with an acidic solution (a solution containing an acid or an oxidizing agent) and a method of subjecting non-graphitic carbon to a plasma treatment. The method of subjecting non-graphitic carbon to a plasma treatment includes, for example, a method of subjecting non-graphitic carbon to an oxidation treatment with a chemical species containing oxygen (e.g., oxygen gas (O2), ozone (O3), oxide ions (O 2- ), oxygen radicals, oxygen plasma, etc.) to the non-graphitic carbon. As the hydrophilized non-graphitic carbon, commercially available products can also be used.

[0048] In the positive electrode active material layer 42, the content of hydrophilized non-graphitic carbon is not particularly limited, but may be more than 4 mass%, may be 4.5 mass% or more, or may be 4.7 mass% or more. In some embodiments, the content of non-graphitic carbon may be, for example, 6 mass% or more, or may be 8 mass% or more. Such a content may be 20 mass% or less, or may be 15 mass% or less. In some embodiments, the content of non-graphitic carbon may be, for example, 12 mass% or less, or may be 10 mass% or less. By making the content of hydrophilized non-graphitic carbon greater than 4 mass %, a binderless positive electrode that does not contain a binder in the positive electrode active material layer 42 can be suitably realized, and a decrease in output of the energy storage element 1 after being left at high temperatures can be further suppressed.

[0049] The positive electrode active material layer 42 may further contain a conductive agent other than hydrophilized non-graphitic carbon (hereinafter also referred to as another conductive agent). The other conductive agent is not particularly limited as long as it is a material having electrical conductivity. Examples of such conductive agents include specific carbonaceous materials, metals, conductive ceramics, etc. Examples of carbonaceous materials include graphite, non-graphitic carbon that has not been hydrophilized, graphene-based carbon, etc. Examples of the non-graphitic carbon include carbon nanofibers, pitch-based carbon fibers, carbon black, etc. Examples of carbon black include furnace black, acetylene black, ketjen black, etc. Examples of graphene-based carbon include graphene, carbon nanotubes (CNT), fullerene, etc. Examples of the shape of the conductive agent include spherical, fibrous, etc. As the conductive agent, one of these materials may be used alone, or two or more of them may be mixed and used. In addition, these materials may be used in combination. For example, a material obtained by combining CNT and non-hydrophilized carbon black may be used. Among these, from the viewpoint of electronic conductivity and coatability, non-hydrophilized carbon black is preferable as the other conductive agent, and non-hydrophilized acetylene black is preferable.

[0050] The content of the other conductive agents in the positive electrode active material layer 42 (the total amount of conductive agents excluding the hydrophilized non-graphitic carbon) is preferably 10 mass % or less, and more preferably 9 mass % or less. When the content of the other conductive agents is within the above range, the energy density of the secondary battery can be further increased. In the present embodiment, it is preferable that the positive electrode active material layer 42 does not contain any conductive agents other than the hydrophilized non-graphitic carbon.

[0051] Examples of thickeners that can be blended in the positive electrode active material layer 42 include polysaccharide polymers such as carboxymethyl cellulose (CMC) and methyl cellulose. When the thickener has a functional group that reacts with lithium or the like, the functional group may be deactivated in advance by methylation or the like. When a thickener is used, the content of the thickener in the positive electrode active material layer 42 is preferably 8 mass % or less, and more preferably 5 mass % or less. The technology disclosed herein can be preferably implemented in an embodiment in which the positive electrode active material layer 42 does not contain the above-mentioned thickener.

[0052] The filler that can be blended in the positive electrode active material layer 42 is not particularly limited. Examples of the filler include polyolefins such as polypropylene and polyethylene, inorganic oxides such as silicon dioxide, alumina, titanium dioxide, calcium oxide, strontium oxide, barium oxide, magnesium oxide, and aluminosilicate, hydroxides such as magnesium hydroxide, calcium hydroxide, and aluminum hydroxide, carbonates such as calcium carbonate, poorly soluble ion crystals such as calcium fluoride, barium fluoride, and barium sulfate, nitrides such as aluminum nitride and silicon nitride, mineral resource-derived substances such as talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, and mica, and artificial products thereof. When a filler is used, the content of the filler in the positive electrode active material layer 42 is preferably 8% by mass or less, and more preferably 5% by mass or less. The technology disclosed herein can be preferably implemented in an embodiment in which the positive electrode active material layer 42 does not contain the above-mentioned filler.

[0053] The positive electrode active material layer 42 may contain, as a component other than the positive electrode active material, the conductive agent, the thickener, and the filler, a substance containing a typical nonmetallic element such as B, N, P, F, Cl, Br, or I; a substance containing a typical metal element such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, Sn, Sr, or Ba; or a substance containing a transition metal element such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Nb, or W.

[0054] The density of the positive electrode active material layer 42 is not particularly limited, but is preferably 1.5 g / cm 3 More than 5.0g / cm 3 It is appropriate that the density is equal to or less than 1.8 g / cm 3 More than 4.0g / cm 3 More preferably, it is 2.0 g / cm 3 More than 3.5g / cm 3 In some embodiments, the density of the positive electrode active material layer 42 is 2.4 g / cm 3 More than 3.2g / cm 3 or less, 2.7 g / cm 3 More than 3.0g / cm 3 If the energy storage device 1 has a positive electrode active material layer 42 with a density within this range, a decrease in output after being left at high temperature can be more sufficiently suppressed.

[0055] The thickness of the positive electrode active material layer 42 (when positive electrode active material layers are formed on both sides of the positive electrode substrate 41, the thickness of only the positive electrode active material layer 42 arranged on one side of the positive electrode substrate 41) is not particularly limited, but is suitably 15 μm or more and 200 μm or less, preferably 20 μm or more and 150 μm or less, and more preferably 25 μm or more and 100 μm or less. In some embodiments, the thickness of the positive electrode active material layer 42 may be 28 μm or more and 80 μm or less, or may be 30 μm or more and 50 μm or less. If the energy storage element 1 has a positive electrode active material layer 42 having a thickness within such a range, the decrease in output after being left at high temperature can be more sufficiently suppressed.

[0056] (Negative electrode) The negative electrode 50 has a negative electrode substrate 51 and a negative electrode active material layer 52 disposed on the negative electrode substrate 51 directly or via an intermediate layer (not shown). The configuration of the intermediate layer is not particularly limited and can be selected from the configurations exemplified for the positive electrode 40. In this embodiment, the negative electrode active material layers 52 are laminated on both sides of the negative electrode substrate 51.

[0057] The negative electrode substrate 51 is conductive. Metals such as copper, nickel, stainless steel, nickel-plated steel, and aluminum, or alloys thereof are used as the material of the negative electrode substrate 51. Among these, copper or a copper alloy is preferable. Examples of the negative electrode substrate 51 include foils and vapor-deposited films, and foils are preferable from the viewpoint of cost. Therefore, copper foil or copper alloy foil is preferable as the negative electrode substrate 51. Examples of copper foil include rolled copper foil and electrolytic copper foil.

[0058] The average thickness of the negative electrode substrate 51 is preferably 2 μm to 35 μm, more preferably 3 μm to 30 μm, further preferably 4 μm to 25 μm, and particularly preferably 5 μm to 20 μm. By setting the average thickness of the negative electrode substrate 51 within the above range, it is possible to increase the strength of the negative electrode substrate 51 and to increase the energy density per volume of the secondary battery.

[0059] The negative electrode active material layer 52 includes a negative electrode active material. The negative electrode active material layer 52 includes optional components such as a conductive agent, a binder, a thickener, and a filler as necessary. The optional components such as the conductive agent, the thickener, and the filler can be selected from the materials exemplified for the positive electrode 40. In this embodiment, the negative electrode active material layer 52 may include the negative electrode active material and a conductive agent. In this case, the conductive agent includes at least hydrophilized non-graphitic carbon, and the negative electrode active material layer 52 may not include a binder.

[0060] Examples of binders that can be included in the negative electrode active material layer 52 include thermoplastic resins such as fluororesins (polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), etc.), polyethylene, polypropylene, polyacrylic, and polyimide; elastomers such as ethylene-propylene-diene rubber (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), and fluororubber; polysaccharide polymers, and the like.

[0061] When a binder is blended in the negative electrode active material layer 52, it is preferable to use an aqueous binder such as ethylene-propylene-diene rubber (EPDM), sulfonated EPDM, or styrene-butadiene rubber (SBR). The content of the binder in the negative electrode active material layer 52 is preferably 1% by mass or more and 10% by mass or less, and more preferably 3% by mass or more and 9% by mass or less. By setting the content of the binder in the above range, the active material can be stably held.

[0062] When a thickener is used in the negative electrode active material layer 52, the content of the thickener in the negative electrode active material layer 52 is preferably 0.5% by mass or more and 8% by mass or less, and more preferably 1% by mass or more and 5% by mass or less. When a conductive agent is used, the content of the conductive agent in the negative electrode active material layer 52 is preferably 8% by mass or less, and more preferably 5% by mass or less. The technology disclosed here can be preferably implemented in an embodiment in which the negative electrode active material layer 52 does not contain the conductive agent. When a filler is used, the content of the filler in the negative electrode active material layer 52 is preferably 8% by mass or less, and more preferably 5% by mass or less. The technology disclosed here can be preferably implemented in an embodiment in which the negative electrode active material layer 52 does not contain the filler.

[0063] The negative electrode active material layer 52 may contain typical nonmetallic elements such as B, N, P, F, Cl, Br, and I, typical metallic elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, Sn, Sr, and Ba, and transition metallic elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Ta, Hf, Nb, and W as components other than the negative electrode active material, conductive agent, binder, thickener, and filler.

[0064] The negative electrode active material can be appropriately selected from known negative electrode active materials. A material capable of absorbing and releasing lithium ions is usually used as the negative electrode active material for a lithium ion secondary battery. Examples of the negative electrode active material include metal Li; metals or semimetals such as Si and Sn; metal oxides or semimetal oxides such as Si oxide, Ti oxide, and Sn oxide; titanium-containing oxides such as Li4Ti5O12, LiTiO2, and TiNb2O7; polyphosphate compounds; silicon carbide; carbonaceous materials such as graphite and non-graphitic carbon (easily graphitized carbon or non-graphitizable carbon). Among these materials, graphite and non-graphitic carbon are preferred. In the negative electrode active material layer 52, one of these materials may be used alone, or two or more of them may be mixed and used.

[0065] "Graphite" refers to graphite that has an average lattice spacing (d 002 ) is 0.33 nm or more and less than 0.34 nm. Examples of graphite include natural graphite and artificial graphite. From the viewpoint of obtaining a material with stable physical properties, artificial graphite is preferred.

[0066] "Non-graphitic carbon" refers to carbon that has an average lattice spacing (d 002 ) is 0.34 nm or more and 0.42 nm or less. Examples of non-graphitizable carbon include non-graphitizable carbon and graphitizable carbon. Examples of non-graphitizable carbon include resin-derived materials, petroleum pitch-derived materials, petroleum coke or petroleum coke-derived materials, plant-derived materials, and alcohol-derived materials.

[0067] Here, the "discharged state" refers to a state in which the open circuit voltage is 0.7 V or more in a single-electrode battery using a negative electrode containing a carbonaceous material as a negative electrode active material as a working electrode and metallic Li as a counter electrode. Since the potential of the metallic Li counter electrode in the open circuit state is approximately equal to the redox potential of Li, the open circuit voltage in the single-electrode battery is approximately equal to the potential of the negative electrode containing the carbonaceous material relative to the redox potential of Li. In other words, the open circuit voltage of 0.7 V or more in the single-electrode battery means that lithium ions capable of being absorbed and released during charging and discharging are sufficiently released from the carbonaceous material, which is the negative electrode active material.

[0068] "Non-graphitizable carbon" means the above d 002 This refers to carbonaceous materials with a particle size of 0.36 nm or more and 0.42 nm or less.

[0069] "Graphitizable carbon" means the above d 002 This refers to carbonaceous materials with a particle size of 0.34 nm or more and less than 0.36 nm.

[0070] The negative electrode active material is usually particulate (powder containing particles). The average particle size of the negative electrode active material can be, for example, 1 nm or more and 100 μm or less. When the negative electrode active material is a carbonaceous material, a titanium-containing oxide, or a polyphosphate compound, the average particle size may be 1 μm or more and 100 μm or less. When the negative electrode active material is Si, Sn, Si oxide, Sn oxide, or the like, the average particle size may be 1 nm or more and 1 μm or less. By setting the average particle size of the negative electrode active material to the above lower limit or more, the negative electrode active material can be easily manufactured or handled. By setting the average particle size of the negative electrode active material to the above upper limit or less, the electronic conductivity of the active material layer is improved. In order to obtain a powder containing particles of a predetermined particle size, a pulverizer, a classifier, or the like is used. The pulverization method and the powder classification method can be selected from, for example, the methods exemplified for the positive electrode 40. When the negative electrode active material is a metal such as metallic Li, the negative electrode active material may be in the form of a foil.

[0071] The content of the negative electrode active material in the negative electrode active material layer 52 is preferably 60 mass % or more and 99 mass % or less, and more preferably 90 mass % or more and 98 mass % or less. By setting the content of the negative electrode active material within the above range, it is possible to achieve both a high energy density of the negative electrode active material layer 52 and ease of production.

[0072] (Separator) The separator 60 can be appropriately selected from known separators. For example, a separator consisting of only a base layer, a separator in which a heat-resistant layer containing heat-resistant particles and a binder is formed on one or both sides of the base layer, etc. can be used as the separator 60. Examples of the form of the base layer of the separator 60 include woven fabric, nonwoven fabric, and porous resin film. Among these, a porous resin film is preferable from the viewpoint of strength, and a nonwoven fabric is preferable from the viewpoint of liquid retention of non-aqueous electrolyte. As the material of the base layer of the separator 60, polyolefins such as polyethylene and polypropylene are preferable from the viewpoint of shutdown function, and polyimide and aramid are preferable from the viewpoint of oxidation decomposition resistance. As the base layer of the separator 60, a material in which these resins are combined may be used.

[0073] The heat-resistant particles contained in the heat-resistant layer preferably have a mass loss of 5% or less when heated from room temperature to 500° C. in an air atmosphere at 1 atm, and more preferably have a mass loss of 5% or less when heated from room temperature to 800° C. in an air atmosphere at 1 atm. Examples of materials with a mass loss of a predetermined value or less include inorganic compounds. Examples of inorganic compounds include oxides such as iron oxide, silicon oxide, aluminum oxide, titanium oxide, barium titanate, zirconium oxide, calcium oxide, strontium oxide, barium oxide, magnesium oxide, and aluminosilicates; hydroxides such as magnesium hydroxide, calcium hydroxide, and aluminum hydroxide; nitrides such as aluminum nitride and silicon nitride; carbonates such as calcium carbonate; sulfates such as barium sulfate; poorly soluble ion crystals such as calcium fluoride and barium fluoride; covalent crystals such as silicon and diamond; mineral resource-derived substances such as talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, and mica, or artificial products thereof. As inorganic compounds, these substances may be used alone or in combination of two or more. Among these inorganic compounds, silicon oxide, aluminum oxide, and aluminosilicate are preferred from the viewpoint of the safety of the energy storage element 1.

[0074] The porosity of the separator 60 is preferably 80% by volume or less from the viewpoint of strength, and is preferably 20% by volume or more from the viewpoint of discharge performance. Here, the "porosity" is a volume-based value, and refers to a value measured with a mercury porosimeter.

[0075] A polymer gel composed of a polymer and a non-aqueous electrolyte may be used as the separator 60. Examples of the polymer include polyacrylonitrile, polyethylene oxide, polypropylene oxide, polymethyl methacrylate, polyvinyl acetate, polyvinylpyrrolidone, and polyvinylidene fluoride. The use of a polymer gel has the effect of suppressing leakage. The separator 60 may be a combination of the porous resin film or nonwoven fabric as described above and a polymer gel.

[0076] (Non-aqueous electrolyte) The nonaqueous electrolyte may be appropriately selected from known nonaqueous electrolytes. The nonaqueous electrolyte may be a nonaqueous electrolyte solution. The nonaqueous electrolyte solution includes a nonaqueous solvent and an electrolyte salt dissolved in the nonaqueous solvent.

[0077] The non-aqueous solvent can be appropriately selected from known non-aqueous solvents. Examples of the non-aqueous solvent include cyclic carbonates, chain carbonates, carboxylates, phosphates, sulfonates, ethers, amides, and nitriles. As the non-aqueous solvent, those in which some of the hydrogen atoms contained in these compounds are substituted with halogens may be used.

[0078] Examples of cyclic carbonates include ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinylene carbonate (VC), vinylethylene carbonate (VEC), chloroethylene carbonate, fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), styrene carbonate, 1-phenylvinylene carbonate, 1,2-diphenylvinylene carbonate, etc. Among these, PC is preferred.

[0079] Examples of the chain carbonate include diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diphenyl carbonate, trifluoroethyl methyl carbonate, bis(trifluoroethyl) carbonate, etc. Among these, DMC and EMC are preferred.

[0080] As the non-aqueous solvent, it is preferable to use a cyclic carbonate or a chain carbonate, and it is more preferable to use a combination of a cyclic carbonate and a chain carbonate. By using a cyclic carbonate, it is possible to promote dissociation of the electrolyte salt and improve the ionic conductivity of the non-aqueous electrolyte. By using a chain carbonate, it is possible to keep the viscosity of the non-aqueous electrolyte low. When using a cyclic carbonate and a chain carbonate in combination, it is preferable that the volume ratio of the cyclic carbonate to the chain carbonate (cyclic carbonate:chain carbonate) is, for example, in the range of 5:95 to 50:50.

[0081] The electrolyte salt can be appropriately selected from known electrolyte salts. Examples of the electrolyte salt include lithium salts, sodium salts, potassium salts, magnesium salts, onium salts, etc. Among these, lithium salts are preferred.

[0082] Examples of the lithium salt include inorganic lithium salts such as LiPF6, LiPO2F2, LiBF4, LiClO4, and LiN(SO2F)2, and lithium salts having a halogenated hydrocarbon group such as LiSO3CF3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9), LiC(SO2CF3)3, and LiC(SO2C2F5)3. Among these, inorganic lithium salts are preferred, and LiPF6 is more preferred.

[0083] The electrolyte salt content in the non-aqueous electrolyte is 0.1 mol / dm at 20°C and 1 atmosphere. 3 More than 2.5mol / dm 3 It is preferable that the value is 0.3 mol / dm or less. 3 More than 2.0mol / dm 3 More preferably, it is 0.5 mol / dm or less. 3 More than 1.7mol / dm 3 More preferably, it is 0.7 mol / dm or less. 3 More than 1.5mol / dm 3 By setting the content of the electrolyte salt within the above range, the ionic conductivity of the nonaqueous electrolyte can be increased.

[0084] The nonaqueous electrolyte may contain additives in addition to the nonaqueous solvent and the electrolyte salt. Examples of additives include halogenated carbonates such as fluoroethylene carbonate (FEC) and difluoroethylene carbonate (DFEC); oxalates such as lithium bis(oxalate)borate (LiBOB), lithium difluorooxalateborate (LiFOB), and lithium bis(oxalate)difluorophosphate (LiFOP); imide salts such as lithium bis(fluorosulfonyl)imide (LiFSI); aromatic compounds such as biphenyl, alkylbiphenyl, terphenyl, partially hydrogenated terphenyl, cyclohexylbenzene, t-butylbenzene, t-amylbenzene, diphenyl ether, and dibenzofuran; partial halides of the aromatic compounds such as 2-fluorobiphenyl, o-cyclohexylfluorobenzene, and p-cyclohexylfluorobenzene; halogenated anisole compounds such as 2,4-difluoroanisole, 2,5-difluoroanisole, 2,6-difluoroanisole, and 3,5-difluoroanisole; vinylene carbonate, methylvinylene carbonate, and the like. carboxylate, ethylvinylene carbonate, succinic anhydride, glutaric anhydride, maleic anhydride, citraconic anhydride, glutaconic anhydride, itaconic anhydride, cyclohexanedicarboxylic anhydride; ethylene sulfite, propylene sulfite, dimethyl sulfite, propane sultone, propene sultone, butane sultone, methyl methanesulfonate, busulfan, methyl toluenesulfonate, dimethyl sulfate, ethylene sulfate, sulfolane, dimethyl sulfone, diethyl sulfone, dimethyl sulfoxide, diethyl sulfoxide , tetramethylene sulfoxide, diphenyl sulfide, 4,4'-bis(2,2-dioxo-1,3,2-dioxathiolane), 4-methylsulfonyloxymethyl-2,2-dioxo-1,3,2-dioxathiolane, thioanisole, diphenyl disulfide, dipyridinium disulfide, perfluorooctane, tristrimethylsilyl borate, tristrimethylsilyl phosphate, tetrakistrimethylsilyl titanate, lithium monofluorophosphate, lithium difluorophosphate, etc. These additives may be used alone or in combination of two or more.

[0085] The content of the additive contained in the non-aqueous electrolyte is preferably 0.01% by mass to 10% by mass, more preferably 0.1% by mass to 7% by mass, even more preferably 0.2% by mass to 5% by mass, and particularly preferably 0.3% by mass to 3% by mass. By setting the content of the additive within the above range, it is possible to improve the capacity retention performance or charge / discharge cycle performance after high-temperature storage, and to further improve safety.

[0086] The non-aqueous electrolyte may be a solid electrolyte, or a non-aqueous electrolyte solution and a solid electrolyte may be used in combination.

[0087] The solid electrolyte can be selected from any material that has ion conductivity such as lithium, sodium, calcium, etc., and is solid at room temperature (for example, 15° C. to 25° C.) Examples of the solid electrolyte include sulfide solid electrolytes, oxide solid electrolytes, oxynitride solid electrolytes, polymer solid electrolytes, etc.

[0088] As the sulfide solid electrolyte, in the case of a lithium ion secondary battery, for example, Li2S-P2S5, LiI-Li2S-P2S5, Li 10 Ge-P2S 12 etc.

[0089] The shape of the energy storage element 1 of this embodiment is not particularly limited, and examples thereof include a cylindrical battery, a square battery, a flat battery, a coin battery, and a button battery. Fig. 1 shows an energy storage element 1 as an example of a prismatic battery. Note that this figure is a see-through view of the inside of a case 3. An electrode body 2 having a positive electrode 40 and a negative electrode 50 wound with a separator 60 sandwiched therebetween is housed in the prismatic case 3. The positive electrode 40 is electrically connected to a positive electrode terminal 4 via a positive electrode lead 45. The negative electrode 50 is electrically connected to a negative electrode terminal 5 via a negative electrode lead 55.

[0090] <Configuration of Nonaqueous Electrolyte Electricity Storage Device> The energy storage element 1 of this embodiment can be mounted as an energy storage unit 10 (battery module) formed by assembling a plurality of energy storage elements 1 in a power source for an automobile such as an electric vehicle (EV), a hybrid vehicle (HEV), or a plug-in hybrid vehicle (PHEV), a power source for electronic devices such as a personal computer or a communication terminal, or a power storage power source, etc. In this case, the technology of the present invention may be applied to at least one energy storage element 1 included in the energy storage device. 3 shows an example of an energy storage device 100 in which energy storage units 10, each of which is an assembly of two or more electrically connected energy storage elements 1, are further assembled. The energy storage device 100 may include a bus bar (not shown) that electrically connects the two or more energy storage elements 1, a bus bar (not shown) that electrically connects the two or more energy storage units 10, and the like. The energy storage unit 10 or the energy storage device 100 may include a status monitoring device (not shown) that monitors the status of the one or more energy storage elements 1.

[0091] <Method of manufacturing the energy storage element> The manufacturing method of the energy storage element 1 of this embodiment can be appropriately selected from known methods. The manufacturing method includes, for example, preparing an electrode body 2, preparing an electrolyte, and assembling an energy storage element by housing the electrode body 2 and the electrolyte in a case 3. Preparing the electrode body 2 includes fabricating a positive electrode 40, fabricating a negative electrode 50, and stacking the positive electrode 40 and the negative electrode 50 with a separator 60 interposed therebetween, and further winding them as necessary to form the electrode body 2.

[0092] In preparing the electrode body 2, the positive electrode 40 is produced by preparing a positive electrode mixture composition containing water, a positive electrode active material, and hydrophilized non-graphitic carbon, preferably using a water-containing solvent (preferably water). No binder is mixed into this positive electrode mixture composition. The prepared positive electrode mixture composition is applied to a positive electrode substrate 41, and the solvent (such as water) is volatilized to form a positive electrode active material layer 42, thereby producing the positive electrode 40. The hydrophilized non-graphitic carbon is easily dispersed in a water-containing solvent because of its hydrophilicity. In particular, the hydrophilized non-graphitic carbon having the above-mentioned hydrophilic functional group (such as an acidic functional group) on the surface is more easily dispersed in a water-containing solvent. Therefore, as described above, the aggregation of the hydrophilized non-graphitic carbon particles is suppressed, and the particles are more sufficiently dispersed, so that a positive electrode active material layer 42 having a good dispersion state can be formed. In particular, when the positive electrode active material containing the above-mentioned nickel-containing lithium transition metal composite oxide is blended into the positive electrode mixture composition, the positive electrode mixture composition tends to be more alkaline, so that a positive electrode active material layer 42 having a good dispersion state can be formed as described above. The method for volatilizing the solvent may be a natural drying method or a heat drying method. The method for volatilizing the solvent is preferably a hot air drying method using a hot air drying oven. By quickly volatilizing the solvent by the hot air drying method, the aggregation of the hydrophilized non-graphitic carbon particles is more sufficiently suppressed, and the positive electrode active material layer 42 in a more uniformly dispersed state can be formed.

[0093] Furthermore, by preparing the positive electrode 40, the hydrophilic functional groups (such as acidic functional groups) present on the surface of the hydrophilized non-graphitic carbon and functional groups such as hydroxyl groups present on the surface of the positive electrode active material can be bonded by dehydration condensation as described above. This bond can occur more frequently when the positive electrode active material layer 42 is formed from a positive electrode mixture composition containing a relatively large amount of water. This makes it possible to more firmly bond the positive electrode active materials together and the positive electrode active materials to the positive electrode substrate 41 via the non-graphitic carbon without using a binder.

[0094] In preparing the electrode body 2, in preparing the negative electrode 50, similarly to the preparation of the positive electrode 40, a negative electrode mixture composition may be prepared using a solvent containing water (preferably water) as the solvent, and the negative electrode active material layer 52 may be formed. On the other hand, a negative electrode mixture composition may be prepared using an organic solvent as the solvent, and the negative electrode active material layer 52 may be formed.

[0095] In preparing the electrode body 2, the electrode body 2 can be formed into a laminated type electrode body or a wound type electrode body by a general method.

[0096] In preparing the non-aqueous electrolyte, for example, a plurality of types of non-aqueous solvents and one or a plurality of types of electrolyte salts are mixed to prepare a non-aqueous electrolytic solution (nonaqueous electrolyte).

[0097] In assembling the energy storage element, a non-aqueous electrolyte is accommodated in the case 3 by a general method appropriately selected from known methods. For example, when a non-aqueous electrolyte solution is used as the non-aqueous electrolyte, the electrode body 2 is accommodated in the case 3, and then the non-aqueous electrolyte solution is injected through an injection hole formed in the case 3, and the injection hole is then sealed.

[0098] <Other embodiments> The energy storage element of the present invention is not limited to the above-described embodiment, and various modifications may be made without departing from the scope of the present invention. For example, the configuration of one embodiment may be added to the configuration of another embodiment, and a part of the configuration of one embodiment may be replaced with the configuration of another embodiment or a well-known technique. Furthermore, a part of the configuration of one embodiment may be deleted. Also, a well-known technique may be added to the configuration of one embodiment.

[0099] In the above embodiment, the case where the energy storage element 1 is used as a chargeable and dischargeable non-aqueous electrolyte secondary battery (for example, a lithium ion secondary battery) has been described, but the type, shape, size, capacity, etc. of the energy storage element are arbitrary. The present invention can also be applied to various secondary batteries, electric double layer capacitors, lithium ion capacitors, and other capacitors.

[0100] In the above embodiment, a detailed description has been given of the energy storage element 1 in which the positive electrode 40 contains hydrophilized non-graphitic carbon and does not contain a binder. However, in other embodiments of the energy storage element, the negative electrode may contain hydrophilized non-graphitic carbon and not contain a binder.

[0101] In the above embodiment, the electrode body 2 in which the positive electrode 40 and the negative electrode 50 are stacked with the separator 60 interposed therebetween has been described, but the electrode body may not include the separator 60. For example, the positive electrode and the negative electrode may be in direct contact with each other in a state in which a non-conductive layer is formed on the active material layer of the positive electrode or the negative electrode. EXAMPLES

[0102] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.

[0103] A non-aqueous electrolyte secondary battery (lithium ion secondary battery) was manufactured as follows.

[0104] (1) Preparation of the positive electrode Example 1 [raw materials] First, a positive electrode active material and a conductive agent were prepared. Positive electrode active material (powder containing active material particles) Nickel-containing lithium transition metal oxide LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 Particle size of secondary particles formed by aggregation of primary particles D50: 4 μm (average particle size D1) Conductive agent (water-dispersed slurry containing hydrophilized non-graphitic carbon) Water-dispersed slurry of hydrophilic carbon black that has been hydrophilically treated Product name: "Aqua-Black162" (manufactured by Tokai Carbon Co., Ltd.) Solid content: 19.2% by mass Average primary particle size of hydrophilic carbon black (average particle size D2): 110 nm Hydrophilic carbon black particles have numerous carboxyl groups on their surface Amount of hydrophilic functional groups determined by the neutralization titration described above: 780 [μmol / g] The pH of the slurry measured by the above method: 6.5 (D2 / D1)=0.03 The particulate positive electrode active material was added to the aqueous slurry containing the hydrophilized non-graphitic carbon, and the mixture was mixed and kneaded. After that, the moisture was removed by hot air drying and vacuum drying to prepare a mixture of the conductive agent and the positive electrode active material. The mixture thus prepared was mixed with water and kneaded to prepare a positive electrode mixture composition. The solid content ratios of the positive electrode active material and the conductive agent were as shown in Table 1. The prepared positive electrode mixture composition was applied to a substrate having a coating amount (weight per unit area) of 8.6 mg / cm after drying. 2 The mixture was applied to one side of an aluminum foil (thickness: 15 μm) serving as a positive electrode substrate, dried, and then roll pressed. Thereafter, the mixture was vacuum dried to volatilize and remove moisture, etc., to form a positive electrode active material layer. The thickness of the positive electrode active material layer (one layer) was 31 μm. The density of the positive electrode active material layer was 2.8 g / cm 3 It was.

[0105] Example 2 A positive electrode mixture composition was prepared in the same manner as in Example 1, except that the compounding ratio of the positive electrode active material and the conductive agent was changed to the values ​​shown in Table 1. The prepared positive electrode mixture composition was applied to one side of an aluminum foil (thickness 15 μm) serving as a positive electrode substrate so that the coating amount (weight per unit area) after drying was 8.2 mg / cm 2 After drying, the mixture was roll-pressed, and then vacuum-dried to volatilize and remove moisture and the like, thereby forming a positive electrode active material layer. The thickness of the positive electrode active material layer (one layer) was 29 μm. The density of the positive electrode active material layer was 2.8 g / cm 3 It was.

[0106] Example 3 Except for using LiFePO4 (particle size D50: 7 μm) as the positive electrode active material, a positive electrode mixture composition was prepared in the same manner as in Example 1. The compounding ratio of the solid content of the positive electrode active material and the conductive agent was the same as in Example 1. The prepared positive electrode mixture composition was applied to one side of an aluminum foil (thickness 15 μm) serving as a positive electrode substrate so that the coating amount (weight per unit area) after drying was 8.3 mg / cm 2After drying, the mixture was roll-pressed, and then vacuum-dried to volatilize and remove moisture and the like, thereby forming a positive electrode active material layer. The thickness of the positive electrode active material layer (one layer) was 38 μm. The density of the positive electrode active material layer was 2.2 g / cm 3 It was.

[0107] Comparative Example 1 N-methyl-2-pyrrolidone (NMP), conductive agent (carbon black [acetylene black] that has not been hydrophilized), binder (PVdF), positive electrode active material (LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, and the particle size D50 of secondary particles formed by aggregation of primary particles: 4 μm) were mixed and kneaded to prepare a positive electrode mixture composition. The solid content ratios of the positive electrode active material, the conductive agent, and the binder were as shown in Table 1. The prepared positive electrode mixture composition was applied to a substrate having a coating amount (weight per unit area) of 8.6 mg / cm after drying. 2 The mixture was applied to one side of an aluminum foil (thickness: 15 μm) serving as a positive electrode substrate, dried, and then roll pressed. Thereafter, the mixture was vacuum dried to volatilize and remove moisture, etc., to form a positive electrode active material layer. The thickness of the positive electrode active material layer (one layer) was 32 μm. The density of the positive electrode active material layer was 2.7 g / cm 3 It was.

[0108] Comparative Example 2 The slurry of hydrophilized carbon black used in Example 1 was mixed with a positive electrode active material (LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2) were mixed and kneaded. After that, the moisture was removed by hot air drying and vacuum drying to prepare a mixture of the conductive agent and the positive electrode active material. The mixture thus prepared was mixed with N-methyl-2-pyrrolidone (NMP) and a binder (PVdF) and kneaded to prepare a positive electrode mixture composition. The solid content ratios of the positive electrode active material, the conductive agent, and the binder were as shown in Table 1. A positive electrode active material layer was formed in the same manner as in Comparative Example 1, except that the above positive electrode mixture composition was used. The basis weight, thickness (for one layer) and density of the positive electrode active material layer were the same as those in Comparative Example 1.

[0109] Comparative Example 3 A positive electrode mixture composition was prepared by mixing and kneading N-methyl-2-pyrrolidone (NMP), a conductive agent (carbon black [acetylene black] that had not been subjected to hydrophilic treatment), a binder (PVdF), and a positive electrode active material (LiFePO4 used in Example 3). The solid content ratios of the positive electrode active material, the conductive agent, and the binder were as shown in Table 1. The prepared positive electrode mixture composition was applied to a substrate having a coating amount (weight per unit area) of 8.3 mg / cm after drying. 2 The mixture was applied to one side of an aluminum foil (thickness: 15 μm) serving as a positive electrode substrate, dried, and then roll pressed. Thereafter, the mixture was vacuum dried to volatilize and remove moisture, etc., to form a positive electrode active material layer. The thickness of the positive electrode active material layer (one layer) was 38 μm. The density of the positive electrode active material layer was 2.2 g / cm 3 (Same as in Example 3).

[0110] (2) Preparation of the negative electrode In all the examples and comparative examples, the same negative electrode was prepared and used in the batteries. The negative electrode active material was non-graphitic carbon particles (non-graphitizable carbon) with an average particle size of 3.3 μm, and PVdF was used as the binder. The negative electrode mixture composition was prepared by mixing and kneading NMP as a solvent, a binder, and an active material. The binder and the active material were mixed so that their solid contents were 7% by mass and 93% by mass, respectively. The prepared negative electrode mixture composition was applied to a substrate having a coating weight (weight per unit area) of 3.95 mg / cm after drying. 2 The coating was applied to one side of a copper foil (thickness: 8 μm) serving as a negative electrode substrate so that the coating became as follows: After drying, the coating was roll pressed and vacuum dried to remove moisture and the like, thereby forming a negative electrode active material layer. The thickness of the negative electrode active material layer (one layer) was 35 μm. The density of the negative electrode active material layer was 1.13 g / cm 3 It was.

[0111] (3) Preparation of the separator In all the examples and comparative examples, the same separator was used in the batteries. A separator (inorganic coated separator) was prepared by coating one side of a 15 μm thick polyethylene microporous membrane (separator substrate) with a 6 μm thick inorganic coating layer (heat-resistant layer). The air permeability of this separator was about 100 sec / 100 cc, and the total thickness was 21 μm.

[0112] (4) Preparation of non-aqueous electrolyte In all the examples and comparative examples, the same non-aqueous electrolyte was used in the batteries. A non-aqueous solvent was prepared by mixing 1 part by volume of each of propylene carbonate, dimethyl carbonate, and ethyl methyl carbonate. LiPF6 was dissolved in this non-aqueous solvent so that the salt concentration was 1 mol / L, to prepare a non-aqueous electrolyte.

[0113] (5) Preparation of evaluation cells (non-aqueous electrolyte secondary batteries) (5-1) LiNi as the positive electrode active material 1 / 3 Co 1 / 3 Mn 1 / 3 The evaluation cell using O2 was prepared in the following manner. The positive electrode, negative electrode, and separator were laminated to prepare an electrode assembly. The positive electrode and negative electrode were arranged so that their active material layers faced each other with the separator interposed therebetween, and the separator was arranged so that the inorganic coating layer faced the positive electrode active material layer. The electrode assembly was then housed in a case made of a metal resin composite film, and a nonaqueous electrolyte was poured into the case, which was then sealed by thermal welding to prepare an evaluation cell. The prepared evaluation cell was charged at a constant current (charging current 3.5 mA, charging time 1 hour, charging temperature 25°C) and allowed to stand at 25°C for 12 hours. It was then charged at a constant current (charging current 3.5 mA, charging temperature 25°C) to 4.2 V and further charged at a constant voltage (charging time 3 hours, charging temperature 25°C) at 4.2 V. It was then discharged at a constant current (discharging current 7 mA, discharging temperature 25°C) to 2.4 V. Next, the battery was charged at a constant current (charging current 3.5 mA, charging temperature 25°C) to an electrical quantity equivalent to 80% SOC, left to stand at 45°C for 15 hours, and then left to stand at 25°C for more than 4 hours, and then discharged at a constant current (discharge current 7 mA, discharge temperature 25°C) to 2.4 V. Thereafter, the battery was charged at a constant current (charging current: 3.5 mA, charging temperature: 25° C.) to an electrical quantity giving 20% ​​SOC, and then allowed to stand at 25° C. for 10 days. (5-2) An evaluation cell using LiFePO4 as the positive electrode active material was prepared by the following method. An evaluation cell was prepared in the same manner as in (5-1) above. The prepared evaluation cell was charged at a constant current (charging current 3.5 mA, charging time 1 hour, charging temperature 25°C) and allowed to stand at 25°C for 12 hours. It was then charged at a constant current (charging current 3.5 mA, charging temperature 25°C) to 3.55 V and further charged at a constant voltage (charging time 3 hours, charging temperature 25°C) at 3.55 V. It was then discharged at a constant current (discharging current 7 mA, discharging temperature 25°C) to 2.0 V. Next, the battery was charged at a constant current (charging current 3.5 mA, charging temperature 25°C) to an electrical quantity equivalent to 80% SOC, left to stand at 45°C for 15 hours, and then left to stand at 25°C for more than 4 hours, and then discharged at a constant current (discharge current 7 mA, discharge temperature 25°C) to 2.0 V. Thereafter, the battery was charged at a constant current (charging current: 3.5 mA, charging temperature: 25° C.) to an electrical quantity giving 20% ​​SOC, and then allowed to stand at 25° C. for 10 days.

[0114] <Evaluation of output performance after exposure to high temperatures> 1. Check capacity 1-1. LiNi as a positive electrode active material 1 / 3 Co 1 / 3 Mn 1 / 3 Cells with O2 The battery was charged at a constant current (charging current: 3.5 mA) to 4.2 V in a thermostatic bath at 25° C., and then charged at a constant voltage of 4.2 V (charging time: 3 hours), after which it was discharged at a constant current (discharging current: 7 mA) to 2.4 V. 1-2. Cells using LiFePO4 as the positive electrode active material The battery was charged at a constant current (charging current: 3.5 mA) to 3.55 V in a thermostatic bath at 25° C., and then charged at a constant voltage (charging time: 3 hours) at 3.55 V, followed by constant current discharge (discharging time: 7 mA) to 2.0 V. 2. Output confirmation test 2-1. LiNi as a positive electrode active material 1 / 3 Co 1 / 3 Mn 1 / 3 Cells with O2 In a thermostatic bath at 25°C, a cell (open circuit voltage 3.65 V) adjusted to SOC 50% was discharged for 10 seconds at a current value of 14 mA, and after a 60-second pause, it was charged with the same amount of electricity as that discharged at a current value of 3.5 mA. After a 300-second pause, discharge tests were carried out at each current value under the same conditions, except that the discharge current value was changed to 28 mA, 42 mA, 56 mA, and 70 mA. Then, the discharge current values ​​were plotted on the horizontal axis and the voltage at one second after the start of discharge at each current value was plotted on the vertical axis, and these were linearly approximated by the least squares method. The slope of the straight line was taken as the cell resistance R. Based on the calculated R, the cell output P was calculated using the following formula. P[W]=2.5× (3.65-2.4) / R 2-2. Cells using LiFePO4 as the positive electrode active material In a thermostatic bath at 25°C, a cell (open circuit voltage 3.18 V) adjusted to SOC 50% was discharged for 10 seconds at a current value of 14 mA, and after a 60-second pause, it was charged with the same amount of electricity as that discharged at a current value of 3.5 mA. After a 300 second pause, discharge tests were carried out at each current value under the same conditions, except that the discharge current value was changed to 28 mA, 42 mA, 56 mA, and 70 mA. Then, the discharge current values ​​were plotted on the horizontal axis and the voltage at one second after the start of discharge at each current value was plotted on the vertical axis, and these were linearly approximated by the least squares method. The slope of the straight line was taken as the cell resistance R. Based on the calculated R, the cell output P was calculated using the following formula. P[W]=2.0×(3.18-2.0) / R 3.High temperature storage test The cell was adjusted to SOC 85% in a thermostatic chamber at 25° C. and then left to stand in a thermostatic chamber at 65° C. for 15 days. Thereafter, the device was left to stand in a thermostatic chamber at 25°C for at least 4 hours, and the above-mentioned output confirmation test was carried out, and the output after 15 days from the start of the test was calculated. Similarly, the output was calculated 30 and 45 days after the start of the high-temperature storage test by repeating the 15-day rest period in the 65°C thermostatic chamber and the output confirmation test. The output before the high-temperature storage test was designated P1, and the output after 45 days was designated P2, and the output degradation rate was calculated using the following formula. Output reduction rate [%]=100-[(P2 / P1)×100] The smaller the output reduction rate [%], the more sufficiently the output reduction is suppressed.

[0115] The evaluation results of the evaluation cells of Examples 1 to 3 and Comparative Examples 1 to 3 are shown in Table 1. In Table 1, carbon black is abbreviated as "CB."

[0116] [Table 1]

[0117] As can be seen from Table 1, in the energy storage elements of the examples, the decrease in output after being left at high temperatures was suppressed. On the other hand, in the energy storage elements of the comparative examples, the decrease in output after being left at high temperatures was not necessarily suppressed. Comparing Example 1 with Example 2, in the energy storage element of the example, the positive electrode active material layer contained more than 4 mass% hydrophilized non-graphitic carbon, and thus the decrease in output after being left at high temperature was sufficiently suppressed. Comparing Example 1 with Comparative Example 1, and comparing Example 3 with Comparative Example 3, it can be said that in the energy storage elements of the Examples, the positive electrode active material layer contains hydrophilized non-graphitic carbon and nickel-containing lithium transition metal composite oxide (positive electrode active material), and thus the decrease in output after being left at high temperature is significantly suppressed. [Explanation of symbols]

[0118] 1: Electric storage element (non-aqueous electrolyte secondary battery), 2: Electrode body, 3: case; 31: case body; 32: lid body; 4: positive terminal, 5: negative terminal, 40: Positive electrode, 41: positive electrode base material, 42: positive electrode active material layer, 50: negative electrode, 51: negative electrode base material, 52: negative electrode active material layer, 45: positive electrode lead, 55: negative electrode lead, 60: separator, 10: power storage unit, 100: power storage device.

Claims

1. An electrode having an active material layer including active material particles, the active material layer contains hydrophilized non-graphitic carbon particles (excluding fibrous carbon particles); The content of the binder in the active material layer is less than 3000 ppm, A storage element, wherein the content of the hydrophilized non-graphitic carbon particles in the active material layer is greater than 4 mass %.

2. The energy storage element according to claim 1 , wherein the active material layer contains particles of a nickel-containing lithium transition metal composite oxide as the active material particles.

Citation Information

Patent Citations

  • Electrode for battery and secondary battery by using it

    JP1999329438A

  • Positive electrode for lithium ion secondary batteries, and lithium ion secondary battery

    JP2015176831A

  • Method for manufacturing electrode material

    JP2015228290A

  • Positive electrode for secondary battery

    JP2020064790A

  • Manufacturing method of positive electrode active material slurry for nonaqueous electrolyte secondary battery

    JP2020068118A